(untitled) (Italian Review of Legal History, 2015)
This paper aims to show how the Napoleonic strategy in criminalibus did not end with the severe penal code of 1810. Along with it, according to Napoleon’s plan from the beginning, there are two other levels of repression, apparently more hidden. Firstly, we allude to the special courts established in 1801 to cope with the spread of banditry, which would later become laid out in the same fabric of the code of penal procedure. A further level of repression would officially emerge only in 1810 with the institutionalization of detention in State prisons. We are dealing with instruments designed to increase the already strong punitive action, levels of repression destined pour cause to dissolve the system of sealed warrants in the penal code and court. It is the author’s opinion that the code of the Napoleonic repressive ordinance, in fact, should be taken in its entirety.